The evolutionary ecology of spiteful bacteriocin production - Inglis, R; Robert Fredrik Inglis (2010)
Understanding the conditions that favour the evolution and maintenance of spiteful bacteriocin production combines two important questions from the fields of social evolution and microbiology. Spiteful behaviours, though, initially thought to be rare represent an important class of interactions between bacteria through the production of bacteriocins. Bacteriocins can be considered spiteful as they are costly to produce (in many cases requiring lysis) and are costly to sensitive bacteria (i.e. they are lethal). However, much about the ecology of spiteful behaviours and bacteriocin production remains unclear. Mathematical models have given us important insights into some conditions that should favour bacteriocin production, but few empirical studies exist supporting these results. In this thesis I use the bacterium Pseudomonas aeruginosa (a prolific producer of bacteriocins), to examine conditions that favour bacteriocin production. I also investigate more specific elements about this system and toxin production in general. I find that bacteriocin production in P. aeruginosa closely follows predictions made from mathematical models under a range of different conditions (e.g. frequency, scale of competition, multiple social traits). I also find that resistance can evolve to bacteriocins and biological mechanisms such as the neutralisation of one’s own toxin can have important consequences. Finally, I consider bacteriocin as a policing trait testing predictions about the role that linkage plays in policing. This work represents a comprehensive study into the importance of bacteriocin production in bacteria.